The prevalence and molecular basis of β-thalassemia in Isparta province and region - Tunç, Bahattin; Çetin, Hasan; Gümrük, Fatma; İstanbullu, Beysun; Yavrucuoğlu, Hasan; Kurt, Umran; Genç, Halide (The Turkish Journal of Pediatrics, 2002)
The prevalence and molecular basis of β-thalassemia in the district of Isparta were determined in a total of 6,054 healthy high school students who were recruited from 21 randomly selected high schools in the Isparta province and region. In 182 subjects, naked eye single tube red cell osmotic fragility test (NESTROFT test) was positive HbA2 was measured by high-performance liquid chromatography (HPLC) in these subjects and was found to be high in 149 subjects. The incidence of β-thalassemia was 149 in 6,054 (25%). The β-thalassemia frequency was lower in the city center than in neighboring towns, 1.7% vs. 2.2%, respectively. The most prevalent mutation of β-thalassemia in this region was IVS 1-110 (G-A), followed by Codon 39 (C-T) and IVSII-745 (C-G).
Keywords: hemoglobinopathy; prevalence; β-thalassemia trait; screening; population